Pengaruh Pelatihan Terhadap Produktivitas Karyawan pada PT.Alfaria Trijaya, Tbk Soekarno-Hatta Bandung - Harun Heri Trismiyanto (Program Studi Manajemen, Universitas Al Ghifari, 2019)
So that labor productivity increased labor, one of the ways that must be taken workforce management is providing training to its workforce. This research is classified into associative research and descriptive research. Associative research is research that aims to determine the relationship between two or more variables. in this study, researchers will explain the variables that would be appropriate that occurred in PT.Alfaria Trijaya, Tbk Bandung.The total number of employees PT.Alfaria Trijaya, Tbk part minimarket service in the Bandung area is a total of about 1500 people. The sample will be taken is 62 people. the data analysis is classifying data based on variables and types of respondents, tabulate the data based on the variables of all respondents, presenting the data of each variable studied, perform calculations to test the hypothesis that has been proposed. The results of multiple correlation analysis showed a correlation value 0892. means of training and productivity of employees have a degree of force that is very strong relationship with work productivity. That assumption is taken from the value of 0, 892 which is in the range of 0.8 to 1.The coefficient of determination used to how big the influence of training on labor productivity. Based on the analysis using SPSS 13:00 KD value obtained is equal to 0796 X 100% = 79.6% of the value shows that the effect of training on labor productivity is 79.6% while the remaining 20.4% influenced by other variables. Based on the calculation result is unknown if the training provides a positive and significant effect on employee productivity. The condition is indicated when an increase in the quality of training will result in an increase in employee productivity.